Creating a community-based comprehensive intervention to improve asthma control in a low-income, low-resourced community. (2nd August 2020) - Bryant-Stephens, Tyra; Kenyon, C.; Apter, A.J.; Wolk, Courtney; Williams, Yolanda S.; Localio, R.; Toussaint, K.; Hui, A.; West, C.; Stewart, Yvonne; McGinnis, S.; Gutierrez, M.; et al.
Abstract: Introduction: Asthma evidence-based interventions (EBI) are implemented in the home, school, community or primary care setting. Although families are engaged in one setting, they often have to navigate challenges in another setting. Objective: Our objective is to design and implement a comprehensive plan which integrates EBI's and connects the four sectors in underserved communities such as Philadelphia. Methods: September 2015-April 2016 we implemented a three-pronged strategy to understand needs and resources of the community including 1) focus groups and key informant interviews, 2) secondary data analysis and 3) pilot testing for implementation to determine gaps in care, and opportunities to overcome those gaps. Results: Analysis of the focus group and key informant responses showed themes: diagnosis fear, clinician time, home and school asthma trigger exposures, school personnel training and communication gaps across all four sectors. EBI's were evaluated and selected to address identified themes. Pilot testing of a community health worker (CHW) intervention to connect home, primary care and school resulted in an efficient transfer of asthma medications and medication administration forms to the school nurse office for students with uncontrolled asthma addressing a common delay leading to poor asthma management in school. Conclusion: Thus far there has been limited success in reducing asthma disparities for low-income minority children. This study offers hope that strategically positioning CHWs may work synergistically to close gaps in care and result in improved asthma control and reduced asthma disparities.